Modulatory effects of Macaranga tanarius leaves on rumen fermentation and fatty acid biohydrogenation in sheep: an in vitro study - Jotham, S.; Muhammad, A. I.; Samsudin, A. A. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study investigated the in vitro rumen fermentation characteristics, metabolism, and apparent biohydrogenation of fatty acids in Macaranga tanarius leaves (MTL) as a potential feed for sheep, compared to Napier grass (NG). Rumen fluid from four cannulated Dorper sheep was used to assess the in vitro fermentation kinetics of 200 mg of each forage. The analysis included gas production, in vitro dry matter and organic matter digestibility (IVDMD and IVOMD), volatile fatty acid (VFA) pro-duction, metabolizable energy (ME), and fatty acid profiles, including biohydrogenation. Metaboliza-ble energy (ME), gas production, and the in vitro digestibility of dry matter (IVDMD) and organic mat-ter (IVOMD) were significantly higher (P < 0.05) for the MTL group than for the NG group. This was accompanied by higher crude protein (CP), ether extract (EE) and non-fibre carbohydrates (NFC) in the MTL group. Conversely, neutral detergent fibre (NDF) and acid detergent lignin (ADL) were nega-tively correlated with CP, IVDMD, and IVOMD (P < 0.001), while strong positive correlations were observed among CO, IVDMD, and IVOMD (P < 0.001). Overall, Macaranga tanarius leaves demon-strated superior in vitro rumen fermentation efficiency, evidenced by enhanced digestibility, energy yield, and biohydrogenation capacity relative to Napier grass. These findings suggest that M. tanarius leaves hold significant promise as a sustainable and nutritious feed resource for sheep, with implica-tions for optimizing ruminant nutrition and productivity.